Peran Strategis Investasi Domestik dan Asing dalam Pengembangan Ekonomi Daerah di Kalimantan Barat - Dewi Puryanti (Ikatan Da'i Indonesia, 2025)
This study aims to analyze the difference in contribution between foreign investment and domestic investment to economic growth in West Kalimantan during the period 2011-2023. The method used is a quantitative approach using secondary data from BKPM and BPS. The analysis was conducted through descriptive statistics and non-parametric Wilcoxon Signed Ranks Test and Mann-Whitney U Test because the normality test results showed the data was not normally distributed. The results show that domestic investment realization is significantly higher than foreign investment, both in terms of value and number of projects. The Wilcoxon test results produce a significance value of 0.001, while the Mann-Whitney test shows a significant difference in the number of projects with a significance value of 0.000. The conclusion of this study is that domestic investment plays a more dominant role in supporting regional economic growth than foreign investment. This finding indicates the need for a more progressive and adaptive policy strategy to increase the attractiveness of foreign investment through the provision of incentives, infrastructure improvements, and synergy of central and regional policies.